1987
DOI: 10.1523/jneurosci.07-06-01799.1987
|View full text |Cite
|
Sign up to set email alerts
|

Laminar and regional distributions of neurofibrillary tangles and neuritic plaques in Alzheimer's disease: a quantitative study of visual and auditory cortices

Abstract: The number of Thioflavine S-positive neurofibrillary tangles (NFT) and neuritic plaques (NP) was determined in visual and auditory cortical regions of 8 patients with Alzheimer's disease. On both a regional and laminar basis, NFT exhibited very distinctive and consistent distribution patterns. The mean (+/- SEM) number of NFT in a 250-micron- wide cortical traverse was very low in area 17, primary visual cortex (0.9 +/- 1.0), increased 20-fold in the immediately adjacent visual association cortex of area 18 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
273
2
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(304 citation statements)
references
References 53 publications
(54 reference statements)
26
273
2
3
Order By: Relevance
“…27,28 Early microscopic studies have described the intracellular and extracellular features of AD in limbic and neocortical brain regions, [29][30][31][32] and more recent MR imaging studies have demonstrated volumetric changes in corresponding gray matter regions of AD brains. 1,[33][34][35][36] However, relatively little attention has been directed toward abnormalities in cerebral white matter in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Early microscopic studies have described the intracellular and extracellular features of AD in limbic and neocortical brain regions, [29][30][31][32] and more recent MR imaging studies have demonstrated volumetric changes in corresponding gray matter regions of AD brains. 1,[33][34][35][36] However, relatively little attention has been directed toward abnormalities in cerebral white matter in AD.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the known propensity for early degeneration of temporal lobe structures such as the hippocampal formation, parahippocampal gyrus, and entorhinal cortex in AD. 1,3,[30][31][33][34] Furthermore, because DA is more strongly related to axonal pathology and DR is more strongly related to demyelination, 18,19 the changes in temporal white matter directional diffusivities of MCI (2DA) may reflect early axonal damage, and the directional diffusivity changes in temporal white matter of AD (2DA, 1DR) may reflect complete loss of myelinated axons as would be seen in wallerian degeneration. Lesser changes in directional diffusivities were also observed in the frontal and parietal white matter of MCI and AD subjects but were not observed in the occipital white matter.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive deficits in AD may be related to a possible disconnection between cortical areas due to pathology affecting neurons that provide long corticocortical connections [13,17,19,22,23]. MCI is considered a risk factor for the development of AD [26], which suggests that less extensive cortical disconnection, relative to AD, may contribute to the memory dysfunction in MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperphosphorylation induces aggregation and then fibrillation, which in humans can progress to NFT formation. In AD, NFTs are selective to the association cortex (7,8), where they specifically target pyramidal cells with the most extensive corticocortical connections (9). For example, layer III pyramidal cells of the dorsolateral prefrontal association cortex (dlPFC) have extensive corticocortical connections and are afflicted early and severely in AD (9).…”
mentioning
confidence: 99%
“…For example, layer III pyramidal cells of the dorsolateral prefrontal association cortex (dlPFC) have extensive corticocortical connections and are afflicted early and severely in AD (9). In contrast, primary sensory cortices (e.g., visual area V1) have very few NFTs even in late-stage disease (7,8). Although this pattern of degeneration has been recognized for decades, it has not been known why extensively interconnected pyramidal cells in association cortex are selectively afflicted and why advancing age is such a high risk factor for their degeneration.…”
mentioning
confidence: 99%